2013
DOI: 10.1097/igc.0000000000000000
|View full text |Cite
|
Sign up to set email alerts
|

Laparoscopic Lymphadenectomy in Advanced Cervical Cancer: Prognostic and Therapeutic Value

Abstract: Para-aortic and pelvic lymphadenectomy provides valuable information about mortality risk in patients with locally advanced cervical cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(7 citation statements)
references
References 40 publications
0
7
0
Order By: Relevance
“…However, there are known limitations of clinical staging using modern 3D imaging techniques such as magnetic resonance imaging (MRI), computed tomography (CT) and integrated 18 F-FDG positron emission tomography-CT (PET-CT) [8][9][10][11]. Regarding PALN involvement, several retrospective studies have demonstrated a significant rate of upstaging by pathologic staging after surgery when compared to staging by imaging of PALNs [3,12,13]. This suggests imaging techniques cannot completely fill the gap between clinical and histological staging.…”
Section: Introductionmentioning
confidence: 99%
“…However, there are known limitations of clinical staging using modern 3D imaging techniques such as magnetic resonance imaging (MRI), computed tomography (CT) and integrated 18 F-FDG positron emission tomography-CT (PET-CT) [8][9][10][11]. Regarding PALN involvement, several retrospective studies have demonstrated a significant rate of upstaging by pathologic staging after surgery when compared to staging by imaging of PALNs [3,12,13]. This suggests imaging techniques cannot completely fill the gap between clinical and histological staging.…”
Section: Introductionmentioning
confidence: 99%
“…Retrospectively, in patients with stage IIB, 17% had positive pelvic nodes and 25.5% positive para-aortic nodes. Furthermore, in patients with stage IIIB, 33% had positive nodes in the pelvic region and 43.5% in the para-aortic region [ 12 ]. Zand et al .…”
Section: Discussionmentioning
confidence: 99%
“…In contrast to the observations presented above, del Pino et al . have suggested that the removal of nodes has no therapeutic benefit [ 12 ]. In the group of patients with para-aortic positive nodes, complete removal of nodes was not associated with a higher mortality risk than para-aortic node sampling alone, although the univariate Cox logistic model indicates that lymph node metastases in both the pelvic and para-aortic areas are associated with an increased risk of death.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several retrospective studies have demonstrated a significant rate of upstaging, mainly determined by nodal or peritoneal spread, as a confirmation of more extensive disease in a substantial proportion of patients when comparing the results of standard clinical staging with pathological features after surgery. 11 , 12 Thus, an individualized extended field of radiation could be implemented to patients according to pathological findings and might be beneficial for their overall survival (OS). 13 …”
Section: Introductionmentioning
confidence: 99%